TEMPO-RHYTHMIC ABILITIES OF THE GYMNASTS AS A FACTOR DETERMINING THE DIFFICULTY OF COMPOSITE SOLUTION OF COMPETITIVE ROUTINE IN GROUP ROUTINES DEPENDING ON THE CHOICE OF MUSICAL ACCOMPANIMENT - Aleksandra Suprun; Elena Medvedeva; Anna Titova; Vera Borisova (Journal of Applied Sports Sciences)
Starting from 2018 the judges began to evaluate the level of difficulty of the compositions with an open scale according to the rules of the competition. The article is devoted to the evaluation of the compositional difficulty of competitive compositions of group routines in rhythmic gymnastics. One of the factors that determines both the difficulty of the composition and the synchronization of motor interaction execution by sportswomen in group routines is defined. The purpose of this research is to justify the necessity of taking into account tempo-rhythmic abilities of gymnasts that predetermine difficulty of compositional decision of competitive program in group routines. The objective of this study is to reveal the correlational interconnections between tempo-rhythmic abilities and expert evaluations of synchronicity of group motor activity. The methods that were applied in are an expert evaluation that assesses the synchronization of motor actions of gymnasts in group routines and testing that consists of listening to and playing of parts of pieces of music of different rhythmic patterns. The revealed correlational interconnections allow increasing the synchronicity of motor actions of gymnasts in group routines that will make competitive programs more qualitative and spectacular.